Fibrin Gel-Immobilized VEGF and bFGF Efficiently Stimulate Angiogenesis in the AV Loop Model - Arkudas, Andreas (ScholarOne, 2007)
The modulation of angiogenic processes in matrices is of great interest in tissue engineering. We assessed the angiogenic effects of fibrin-immobilized VEGF and bFGF in an arteriovenous loop (AVL) model in 22 AVLs created between the femoral artery and vein in rats. The loops were placed in isolation chambers and were embedded in 500 μL fibrin gel (FG) (group A) or in 500 μL FG loaded with 0.1 ng/μL VEGF and 0.1 ng/μL bFGF (group B). After two and four weeks specimens were explanted and investigated using histological, morphometrical, and ultramorphological [scanning electron microscope (SEM) of vascular corrosion replicas] techniques. In both groups, the AVL induced formation of densely vascularized connective tissue with differentiated and functional vessels inside the fibrin matrix. VEGF and bFGF induced significantly higher absolute and relative vascular density and a faster resorption of the fibrin matrix. SEM analysis in both groups revealed characteristics of an immature vascular bed, with a higher vascular density in group B. VEGF and bFGF efficiently stimulated sprouting of blood vessels in the AVL model. The implantation of vascular carriers into given growth factor-loaded matrix volumes may eventually allow efficient generation of axially vascularized, tissue-engineered composites.